THE INHERITANCE OF YIELD AND YIELD COMPONENTS OF FIVE WHEAT HYBRID POPULATIONS UNDER DROUGHT CONDITIONS - Ahmed, Nisar; Chowdhry, Muhammad Aslam; Khaliq, Ihsan; Maekawa, Masahiko (Indonesian Journal of Agricultural Science, 2007)
The magnitude of genetic inheritance and expected genetic advanceare important for the prediction of response to selectionin diverse environments and provide the basis for planning andevaluating breeding programs. This work investigated the inheritanceof traits related to drought in wheat under naturaldrought conditions. Cross combinations were made to produceF1 and F2 hybrid populations, which were evaluated in a randomizedcompleted block design with three replications at Universityof Agriculture, Faisalabad, Pakistan. Six wheat varieties/linesand six derived F2 hybrids were studied to ascertain heritabilityand genetic advance for plant height, days taken to maturity,number of tillers per plant, spike length, number of grains perspike, 1000-grain weight, and grain yield per plant. Data werecollected and subjected to statistical genetic analyses. Heritabilityestimates and expected genetic advance for plant height,days taken to maturity, number of tillers per plant, 1000-grainweight and grain yield per plant were high for the entire crosscombinations while the estimates for spike length and numberof grains per spike were relatively low. Our results suggest thatimprovement for these characters should be faster because ofhigher heritabilities and greater phenotypic variation. Prospectsof genetic improvement for all the characters studied are evident.The most promising cross combinations were WL60 Ã LU26Sand WL61 Ã LU26S. These traits, therefore, deserve better attentionin future breeding programs for evolving better wheatfor stress environments.[Keywords: Triticum aestivum, plant breeding, drought resistance,yield components, genetic gain, heritability]